Multiple Measures of Mineral Metabolism Were Associated With Renal Function in Chinese Centenarians: A Cross-Sectional Study - Fu, Shihui; Yu, Haotian; Li, Yulong; Lv, Faqin; Deng, Juelin; Zhang, Fu; Luan, Fuxin; Zhao, Yali; Yao, Yao (Frontiers in Medicine, 2020)
Background: Chronic kidney disease (CKD) constitutes a public health issue that is estimated to affect more than 10% of global population, and over one hundred million people have CKD in China. As the first time, this cross-sectional study was designed to determine whether multiple measures of mineral metabolism had significant association with renal function in Chinese centenarians. Methods: China Hainan Centenarian Cohort Study was conducted in 18 cities and counties of Hainan Province, China. It utilized the standard methodology for home interview and blood analyses in 750 centenarians including 608 females and 142 males. Results: All centenarians have a median (range) age of 102 (100-115) years, and median (range) level of estimated glomerular filtration rate (eGFR) was 63 (16-138) ml/min/1.73 m2. There were 318 centenarians (42.4%) with eGFR levels <60 ml/min/1.73m2. In simple correlation and multivariate linear regression analyses, serum phosphorus, osteocalcin, β-crosslaps, total procollagen type 1 N-terminal propeptide (TP1NP) and parathyroid hormone (PTH) levels were negatively associated with eGFR levels (P<0.05 for all). Conclusion: The current study supported that serum phosphorus, osteocalcin, β-crosslaps, TP1NP and PTH levels were negatively associated with eGFR levels, and demonstrated significant association between multiple measures of mineral metabolism and renal function in Chinese centenarians.